Childhood Maltreatment and Narcissism: The Mediating Role of Dissociation - Spägele, Nina (Journal of interpersonal violence, 2022)
Childhood maltreatment (CM) is thought to be linked to adult narcissistic traits. However, it remains unclear how CM is associated with each type of narcissism, vulnerable and grandiose, and what mechanism mediates these links. One potential candidate is dissociation. This study examines the relations among CM, dissociation, vulnerable narcissism, and grandiose narcissism. A total of 322 women completed self-reported questionnaires assessing CM, dissociation, vulnerable narcissism, and grandiose narcissism. To examine the relations among CM, dissociation, and each type of narcissism, we performed Pearson?s correlations and mediation analyses. In secondary analyses, we conducted latent class analyses to classify different types of CM and to assess their relations with the study variables. We found small to moderate correlations between CM and vulnerable narcissism, (r = .35, p < .001) and CM and grandiose narcissism (r = .2, p < .001), with the former association being greater than the latter (z = ?3.25, p < .001). Dissociation was found to mediate the link between CM and each type of narcissism (p < .001). Results suggest that CM may play a role in the etiology of vulnerable and grandiose narcissism, and that dissociation links CM to each type of narcissism. Findings highlight that CM may lead to different responses in terms of narcissism?through the same mediation process.